The influence of habitat structure on fish assemblages in Amazonian streams of Machado river basin - da Costa, Igor David; Rocha, Vanessa (Revista de Biología Tropical, 2017)
Igarapés are Amazonian streams that are extremely susceptible to environmental changes. Due to the rapidly occurring riparian land use changes, and the several impacts these may have on fish assemblages, it is highly valuable to describe and understand the current relationships between these assemblages and the local environmental conditions, especially in barely know areas. In this research, we studied the taxonomic composition and fish assemblage attributes variation in three streams with different riparian conservation conditions: forest, intermediate and pasture. Samplings were performed every two months from October 2011 to September 2012, in three 1st order streams in the Machado River Basin, Rondônia. Fish were collected using trawls (seine net with a mesh size of 2 mm) and dip nets (2 mm mesh) along the entire stretch; the obtained samples were preserved and identified per site type. A total of 2 141 fish specimens belonging to 59 species, 17 families and five orders were recorded. Unlike the intermediate and pasture streams, the forest stream showed a high richness and low abundance. The forested stream exhibited the highest diversity and evenness value, and had low dominance, unlike the other streams. The variance partitioning and partial Redundancy Analysis (pRDA) indicated that assemblage composition was significantly explained by the environmental variables such as: depth, water velocity, pteridophytes and grasses, but not by spatial predictors. The non-metric multidimensional scaling (NMDS) analysis showed that intermediate and pasture streams separated from the forested stream. We concluded that both, the stream environmental variables and fish assemblage attributes were influenced by the different conservation status and land cover. Given the influence of regional processes, which have a pervasive role in local fish assemblages, land use at the watershed scale is important, especially to explain the higher richness and diversity found in forested streams.